Clinical and genetic characteristics associated with dual-positive gene variations - Li Wang; Jinghe Shi; Xiaojing Yin; Pingyun Qiao; Fuwei Li; Weixing Feng (Frontiers in Neuroscience, 2025)
ObjectiveTo analyze the clinical and genetic characteristics associated with dual-positive gene variations.MethodsA retrospective analysis was conducted on two children diagnosed with dual-positive gene variations.ResultsPatient 1, a 7-year-old girl, presented with a low hairline, microcephaly, high-arched eyebrows, thick eyebrows, a short nasal bridge, a thin and red upper lip, and a high palatal arch. She exhibited delayed language and motor development. Genetic analysis revealed a de novo variation in the SMC3 and MECP2 genes. Patient 2, a 1.5-year-old boy, exhibited high-arched eyebrows, long eyelashes, large ears, microcephaly, a single transverse palmar crease, a curved fifth finger, tremors in the hands and feet, external rotation of both feet, and a staggering gait. He was unable to squat, had reduced muscle strength in the distal lower limbs, and electromyography suggested neurogenic damage. Additional findings included patent ductus arteriosus and mild auditory abnormalities. Genetic analysis identified a de novo variation in the SMC3 gene and a 1.38 Mb pathogenic haploid duplication at the PMP22 gene in both the proband and his father. The PMP22 gene duplication was also present in his cousin, aunt, and grandfather.ConclusionWe identified a rare case of a child with Cornelia de Lange Syndrome type 3 (CDLS3), accompanied by severe cognitive impairment, attributed to variations in the SMC3 and MECP2 genes. The MECP2 gene variation, while not resulting in Rett syndrome, may exacerbate the cognitive impairment. Additionally, we observed a rare instance of CDLS3 co-occurring with Charcot–Marie–Tooth disease type 1A. In situations where a single gene cannot be accounted for the clinical phenotype, it is imperative to consider the potential involvement of additional genetic variations.